Computational Methods for Optimal Design and Control 1998
DOI: 10.1007/978-1-4612-1780-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Disturbances in Boundary Layers

Abstract: Streamwise streaks are ubiquitous in transitional boundary layers, particularly when subjected to freestream turbulence. Using the steady boundary-layer approximation, we numerically calculate the upstream disturbances experiencing maximum spatial energy growth. The calculations use techniques commonly employed when solving optimal-control problems for distributed parameter systems. The calculated optimal disturbances consist of streamwise vortices developing into streamwise streaks. The maximum possible energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…As in the present study the observed streak growth in all these investigations agrees well with the theory of non-modal growth. Moreover, Andersson et al (1997) found good agreement with the experimental results by Westin et al (1994) when they investigated spatial non-modal growth.…”
Section: 2supporting
confidence: 80%
See 1 more Smart Citation
“…As in the present study the observed streak growth in all these investigations agrees well with the theory of non-modal growth. Moreover, Andersson et al (1997) found good agreement with the experimental results by Westin et al (1994) when they investigated spatial non-modal growth.…”
Section: 2supporting
confidence: 80%
“…In a physical experiment or a spatial simulation, however, disturbances grow in space. Recently non-modal growth in boundary layers has been considered in spatial formulations by Luchini (1996) and Andersson, Berggren & Henningson (1997. They found in their analyses that the maximum possible energy growth scales linearly with the distance from the leading edge.…”
Section: Non-modal Growthmentioning
confidence: 99%
“…In particular, Andersson et al (1998aAndersson et al ( , b, c, 1999a have calculated the optimal perturbations of a flat-plate boundary layer by a similar backtracking optimization technique, the main difference being that their energy ratio is defined as in (12) rather than in the Reynolds-independent form of (14), whereas their mathematical model is still constituted by the boundary-layer equations. They thus obtained steady amplification spectra in which dependence on the Reynolds number is accounted for in the definition of energy but not in the model equations.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of spatial stability was recently tackled by Luchini [13,14] and Andersson et al [15,16]. They found that the optimal initial disturbance is composed of stationary streamwise vortices whereas the induced velocity field is dominated by streamwise streaks.…”
Section: Previous Work On Algebraic Growthmentioning
confidence: 99%